Thinking and rethinking the child protection system. Mentoring, an unexplored enough resource - Mihaela Tomita; Roxana Ungureanu (Technium Social Sciences Journal, 2020)
Site-based youth mentoring programs provide a unique context for positive youth development. Conceptually, youth derive benefit not only from the mentor alliance (i.e., youths’ feelings of compatibility with the mentor and satisfaction with the mentoring relationship), but also from their sense of belonging within the program. This paper is based on an international Erasmus + project, titled Now What?: Preparing and Empowering Youth Leaving Care Now What?: Preparing and Empowering Youth Leaving Care, implemented in four European countries (Albania, Greece, Portugal and Romania). One of the major components on the project was to develop a mentoring protocol which was applied in all four countries in the partnership. The results shown us, as anticipated, youth in the high mentor alliance-high belonging group described contributive experiences consistent with high-quality mentor characteristics (e.g., empathy, acceptance) and high-quality settings (e.g., positive social norms, support for efficacy and mattering). In contrast, youth in the low mentor alliance-low belonging group described mentors who were insensitive and noted difficulty connecting with peers.